Exploring english for young learners (EYL) pre-service teachers' experiences: Innovations during their teaching practicum - Setyaningrum, Rina Wahyu; Purwati, Oikurema; Sabgini, Kharisma Naidi Warnanda (JEES (Journal of English Educators Society), 2022)
Innovation related to Teaching English to Young Learners (TEYL) provide opportunities for learners to gain experience using English contextually. This is the implication of the new paradigm of English as an International Language (EIL) in which learning English is no longer aimed at forming learners to speak as the native speakers. Therefore, innovations in TEYL is needed to answer the challenges of changing the status of English in Primary Schools (SD) from subject to extra-curricular. Referring to lesson plans developed by pre-service EYL teachers (PSTs), observation and interviews, the innovations in thematic lessons for TEYL were investigated. The findings showed that all lesson plans have been integrating innovations, including character building in accordance with the 2013 curriculum and intercultural competency that are important for language learning. To interact in the classroom, first language (L1) was used with colloquial variation, code-mixing and code-switching as well as translation. In conclusion, the innovative lessons for TEYL has been practiced by prospective primary school English teachers for preparing themselves to teach at the real school setting after their graduation. It is suggested that further research will be carried out at primary schools participated by in-service teachers and focused on each innovation in order to find TEYL innovative models. HIGHLIGHTS: The study recognizes a shift in the paradigm of Teaching English to Young Learners (TEYL) due to the emergence of the new paradigm of English as an International Language (EIL). English for Young Learners (EYL) requires the teachers’ creativity in teaching it. Innovative EYL classes could be characterized by the selection of intelligent themes or topics, ways for delivering new knowledge while giving young learners with context-based English experience, and less demanding evaluation.